qanda-logo
search-icon
Símbolos
Problema
solution-image
En cada caso, efectuar el producto $coFresp0ndiente$ $\left(-x\right)\left(4x+5\right)=$ $\left(3y+7\right)$ $\left(-4y\right)=$ $\left(-x^{2}\right)\left(2x^{2}+3\right)=$ $\left(2y\right)$ $\left(2y-1\right)=$ $\left(x^{2}-x+2\right)$ $\left(-1\right)=$ $\left(-2m\right)\left(3m^{2}-2m+1\right)=$ $\left(y^{2}-5y-7\right)\left(-1\right)=$ $\left(-x^{2}\right)$ $\left(2x^{2}+3x-1\right)=$ $\left(-2\right)$ $\left(2a^{2}-a-5\right)$ $=$ $\left(2m\right)\left(4m^{2}-6m+9\right)=$
Bachillerato
Otra
Búsquedas: 142
Solución
answer-user-profile-image
Profesor de Qanda - JoseAC
answer-reply-image
?